Contextualizing Health and Aging in the Americas Effects of Space, Time and Place - Vega, William A.; Angel, Jacqueline L.; Gutiérrez Robledo, Luis Miguel F.; Markides, Kyriakos S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents new insights into the consequences of the impending growth in and impact of the older segment of aging communities on local economies. It uses a comparative research framework to further our understanding of issues in health and aging in the transnational context of the health and migratory experience of the U.S.- Mexican population. It also provides an important contribution to the interdisciplinary investigation of new conceptual and methodological approaches in comparative studies (inter-group comparisons) of Hispanic aging and health research. Specifically, the chapters employ different methodologies to address issues related to immigration processes, family and household structure, macroeconomic changes in the quality of community life, and focus on the new realities of aging in Latino families in local communities. The book focuses on measurement, data-quality issues, new conceptual modeling techniques, and longitudinal survey capabilities. As such it is of interest to researchers and policy makers in social sciences and public health.
Part 1: The Role of Place and Environment -- Chapter 1. Population Aging and Health in Puerto Rico (Brian Downer) -- Chapter 2. Regional Disparities in ADL Limitations among Older Latinos, Blacks, and Whites in the United States (William A. Vega) -- Chapter 3. Importa Dónde Vivimos? How Regional Variation Informs our Understanding of Diabetes and Hypertension Prevalence among Older Latino Populations (Catherine García) -- Chapter 4. Latino and Alzheimer's: Social Determinants and Personal Factors Contributing to Disease Risk (Shinyi Wu) -- Chapter 5. Cognitive Functioning of U.S. Adults by Race and Hispanic Origin (Carlos Díaz-Venegas) -- Part 2: Place and Unmet Needs -- Chapter 6. Immigration Enforcement, Older Latino Immigrants, and Implications for Health (Nestor Rodriguez) -- Chapter 7. Medicaid Long-term Community Care in California and Texas: A Growing Fiscal Challenge in a New Era (Jacqueline L. Angel) -- Chapter 8. Strengthening Solidarity: A Theoretical Inquiry into the Roles of Civil Society Organizations in the Support of Elderly Citizens in Mexico City (Ronald J. Angel) -- Chapter 9. The Magnitude of Health Inequalities among Older Adults in Brazil and Mexico (Flávia Cristina Drumond Andrade) -- Part 3: Contextual Elements for Successful Aging -- Chapter 10. Lessons Learned from the Positive Minds - Strong Bodies Trial on Disability Prevention for Racial/Ethnic Minority Elders (Naomi Ali) -- Chapter 11. Older Latinos' Financial Security: Resources, Needs, and Future Prospects (Richard W. Johnson) -- Chapter 12. Disability and the Immigrant Health Paradox: Gender and Timing of Migration (Marc A. Garcia) -- Chapter 13. Limited but Not Disabled: Subjective Disability versus Objective Measurement of Functional Status and Mortality Risk among Elderly Mexican Americans (Phillip A. Cantu) -- Part 4: Caregiving and Family Dynamics -- Chapter 14. Neighborhood Cohesion and Caregiver Well-Being among the Mexican-origin Population (Sunshine Rote) -- Chapter 15. Population Aging inCuba: Coping with Social Care Deficit (Blandine Destremau) -- Chapter 16. Determinants of Informal Care Supply for Older Adults in Yucatan, Mexico (Sean Angst) -- Chapter 17. The Caregiving Experience of Older Mexican Americans and their Caregivers (David V. Flores).
Keywords: Aging; Public health; Population -- Economic aspects; Human geography; Ageing; Public Health; Population Economics; Human Geography